Competitive Approach in Managerial Leadership Psychology - Vasily Vasilievich Belov; Elizaveta Vasilievna Belova (Управленческое консультирование)
This article is devoted to the one of the managerial leadership psychology’s problem: managerial leadership abilities. There is a competitive approach’s critical review about managerial leadership in organization. According this point of view leadership’s ability is the only one special personality quality. There are empirical frameworks of managerial leadership giftedness psychological concept.